PERBANDINGAN PENGARUH LATIHAN MENGGIRING BOLA ANTAR BIDANG DENGAN LATIHAN LOMBA SLALOM MENGGIRING BOLA TERHADAP KETERAMPILAN MENGGIRING BOLA DALAM PERMAINAN SEPAK BOLA PADA SSB JUNIOR PEKANBARU - Mayen yunefri; Selamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, Form reseath was conducted to determine whether there is influence between the dribble exercise field with a slalom race on dribbling skills on SSB Junior Pekanbaru. reseath residents are athletes SSB Junior Pekanbaru. Athletes in this reseath is 18 people. Instrument in this research aims to improve the skills of dribbling. Then the data is processed with statistics, normality test with Liliefors test at a significant level α = 0.05. Based on the analysis of the initial test data, then the effects of exercise across the field to dribble dribbling skills on SSB Junior Pekanbaru show the results as follows: a score of 19.54 seconds the fastest and slowest score was 23.5 seconds, with an average of 21.004. And a standard deviation of 1.161. Based on the frequency distribution table Rabel 1 of 9 samples turned out to be as much as 2 people (22.22%) with the interval from 19.54 to 20.44 range. Then 4 people (44.44%) with the interval ranges from 20.45 to 21.35, while one person (11.11%) with the interval ranges from 22.27 to 23.17. Of calculation has been done shows that the practice dribbling between the field and practice dribbling slalom race together showed an increase in the skills of dribbling, this means that the profits after menggring exercises and drills the ball across the field of competition slalom dribble that as the increase dribbling skills.Key Words: the dribble field, with a slalom race, dribbling skills